Use of assistive technologies as a communication tool in the dental care of children with ASD: Integrative literature review - Patriota, Thaís Marinho; da Silva, Andressa Joselma Santiago; Vasconcelos, Lívia Thamyris de Souza Silva; Ribeiro, Carlos Eduardo Nunes; Nogueira, Maria Lívia Alves; Rocha, Maria Luiza Lima; Andrade, Edilyn Endy Ferreira dos Santos; Borba, Suellen Mariana Vieira; Silva, Giovanna de Lima; de Assunção, Tallita Silva; Bernardino, Geysiane de Andrade; Vasconcelos, Rafaela Brito (Seven Editora, 2024)
Autism Spectrum Disorder (ASD) is a set of neurodevelopmental disorders, identified from deficits in communication and social interaction, as well as restricted and repetitive behavioral patterns. The dental management of ASD requires individualization and a deep understanding of the child's behavioral profile, in which he makes use of several management techniques specific to pediatric dentistry. The lack of utensils and resources for specific care of these patients is a problem. The present study aimed to perform a narrative review of the literature regarding assistive technologies (ATs) as a tool for communication between dental surgeon and patient. Searches were used through the Virtual Health Library - VHL PubMed, SciElo, Lilacs and VHL databases, using the following descriptors: "Autism Spectrum Disorder", "Pediatric Dentistry", "Communication Accessibility" and "Dental Technology" and their counterparts in English and Spanish, within the period of the last 5 years. Additionally, the 2019 Guide for Oral Health Care for People with Disabilities, from the Ministry of Health, was consulted. AT ranges from a simple, low-tech device, such as a magnifying glass, to a complex high-tech device, such as a computerized communication system. The PEC's system, Picture Exchange Communication System, is a promising and very useful tool for the communication of the professional and his patient, especially non-verbal ones. There are also highly complex technologies, such as applications that facilitate communication. ED emerge as communication facilitators for people with disabilities or who have limitations in their communication with the aim of increasing independence, improving interaction and communication when used in the care of patients with ASD. Although it needs more studies in this area, assistive technologies are resources that help in the patient's comfort and communication and that, if well worked by the dentist, can offer a successful treatment. DOI:https://doi.org/10.56238/sevened2024.026-014